Solve for x if ln (x + 1) = 1 + ln x. Solve for x if ln (x + 1) = 1 + ln x. A. $\dfrac{1}{e - 1}$ C. $e + 1$ B. $e$ D. $e^2$ Log in or register to post comments Solution Click here to… Jhun Vert Fri, 06/07/2024 - 21:01 Solution Click here to expand or collapse this section $\ln (x + 1) = 1 + \ln x$ $\ln (x + 1) = \ln e + \ln x$ $\ln (x + 1) = \ln ex$ Hence, $x + 1 = ex$ $1 = ex - x$ $(e - 1)x = 1$ $x = \dfrac{1}{e - 1}$ ← answer Log in or register to post comments

Solution Click here to… Jhun Vert Fri, 06/07/2024 - 21:01 Solution Click here to expand or collapse this section $\ln (x + 1) = 1 + \ln x$ $\ln (x + 1) = \ln e + \ln x$ $\ln (x + 1) = \ln ex$ Hence, $x + 1 = ex$ $1 = ex - x$ $(e - 1)x = 1$ $x = \dfrac{1}{e - 1}$ ← answer Log in or register to post comments

## Solution Click here to…